2021
DOI: 10.1186/s12885-021-07857-x
|View full text |Cite
|
Sign up to set email alerts
|

ETV4 plays a role on the primary events during the adenoma-adenocarcinoma progression in colorectal cancer

Abstract: Background Colorectal cancer (CRC) is one of the most common cancers worldwide; it is the fourth leading cause of death in the world and the third in Brazil. Mutations in the APC, DCC, KRAS and TP53 genes have been associated with the progression of sporadic CRC, occurring at defined pathological stages of the tumor progression and consequently modulating several genes in the corresponding signaling pathways. Therefore, the identification of gene signatures that occur at each stage during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…For many different cancers, patients with higher ETV4 expression had worse disease prognosis. These data were in accordance with previous studies ( 25 – 27 ). Many studies have confirmed that disordered immunity, MMR genes, and DNA methyltransferases contribute to cancer progression and therapeutic outcome ( 28 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…For many different cancers, patients with higher ETV4 expression had worse disease prognosis. These data were in accordance with previous studies ( 25 – 27 ). Many studies have confirmed that disordered immunity, MMR genes, and DNA methyltransferases contribute to cancer progression and therapeutic outcome ( 28 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…4g), which is 15 known to promote metastasis and cause chemotherapeutic drug resistance in CRC 60 . Additionally, it has been shown that the knockdown of ETV4 leads to a decline in cell proliferation and migration in CRC cell lines 61 . DCN can potentially have an influence on ETV4 activity via the MAPK pathway 62 or again via the downstream signaling of the SRC kinase family (Fig.…”
Section: St Charts Cell-to-cell Communication Processes Modulating Cm...mentioning
confidence: 99%
“…The ETV4, also known as ETS variant 4, is a transcription factor that belongs to the ETS transcription factor family and is involved in the regulation of various cellular processes such as cell proliferation, migration, invasion, and differentiation. Studies have shown that over-expression of ETV4 is associated with the progression of different types of cancers, including CRC [73, 74].…”
Section: Discussionmentioning
confidence: 99%